A kind of enhanced polyoxyethylene solid electrolyte and preparation method thereof

By preparing and enhancing polyoxyethylene solid electrolyte, using the three-dimensional frame LLZAO and multi-stage solid electrolyte structure, the safety hazards of liquid electrolytes in lithium-ion batteries and the problem of insufficient stability of solid electrolytes is solved, and a solid-state battery with high conductivity, long life and high safety is achieved.

CN119029330BActive Publication Date: 2025-03-14TIANNENG BATTERY GROUP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411476371.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-03-14
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The liquid electrolytes used in existing lithium-ion batteries have safety risks, such as easy leakage, flammability, and easy decomposition under high temperature and high pressure, and the mechanical and electrochemical stability of solid electrolytes is insufficient, which limits its application.

Method used

Using enhanced polyoxyethylene solid electrolyte, a three-dimensional frame LLZAO is prepared and condensation and cross-linking reaction with bis-3-methacryloxypropylated tetramethyldisiloxane, thiol polyethylene glycol thiol, polyethylene oxide, LiTFSI, succinidine, sodium ethylate and cerium acrylate is formed to form a multi-stage solid electrolyte structure, improving the mechanical stability and lithium ion conduction properties of the electrolyte.

Benefits of technology

It significantly improves the conductivity and discharge specific capacity of solid-state batteries, extends the service life and stability of the battery, inhibits the growth of lithium dendrites, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a reinforced polyethylene oxide solid electrolyte and a preparation method thereof. Part of the thiol groups in the thiol polyethylene glycol thiol group reacts with the propenyl group in the three-dimensional framework LLZAO containing a propenyl group, and the remaining part of the thiol groups in the thiol polyethylene glycol thiol group reacts with the propenyl group in cerium acrylate to play a cross-linking role. The multi-level solid electrolyte structure design effectively isolates the direct contact between succinonitrile and the lithium anode, prevents adverse reactions at the interface, and thus prolongs the service life and stability of the battery. The solid electrolyte prevents the growth of lithium dendrites through its physical barrier effect, because its higher modulus can effectively inhibit the irregular diffusion of lithium in the electrolyte and improve the safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a reinforced polyethylene oxide solid electrolyte and a preparation method thereof. Background Art

[0002] At present, the organic electrolytes used in lithium-ion batteries have safety hazards such as easy leakage, flammability, and easy decomposition under high temperature and high pressure. Using solid electrolytes to replace the current liquid electrolytes can make lithium-ion batteries have higher energy density, longer cycle life and better thermal stability. It is an effective measure to solve the safety problems of lithium-ion batteries and improve energy density.

[0003] The invention application with publication number CN117525560A discloses a method for preparing a LLZO solid electrolyte, comprising: dissolving lithium salt, lanthanum salt, zirconium salt and aluminum salt in water, stirring to obtain solution A; adding a complexing agent and a morphology regulator to the solution A, stirring to obtain solution B; heating solution B in a water bath to obtain a gel; drying the gel to obtain a precursor powder; calcining the precursor powder to obtain a sheet-like LLZO solid electrolyte; the mass fraction relationship of the morphology regulator, the complexing agent and the total metal salt ions in solution B is: 3~8:1~2:5~10. By mixing the morphology regulator, the complex, the lithium salt, the lanthanum salt, the zirconium salt and the aluminum salt in a certain proportion, the prepared LLZO solid electrolyte has a sheet-like two-dimensional morphology.

[0004] The invention application with publication number CN117878393A discloses a method for rapidly preparing a room temperature cubic phase LLZO solid electrolyte, comprising the following steps: (1) weighing a lithium source, a lanthanum source, and a zirconium source, mixing the lithium source, the lanthanum source, the zirconium source and a molten salt, and ball milling the mixture to obtain a mixture; (2) placing the mixture in a muffle furnace for sintering; during this process, the raw material mixture will undergo a chemical reaction to form a crystal structure of the LLZO solid electrolyte; (3) washing the sintered mixture obtained in step (2) with an eluent to remove the molten salt and other impurities, then filtering to remove the residual liquid to obtain a wet solid, and vacuum drying the wet solid to obtain the solid electrolyte.

[0005] Inorganic solid electrolytes generally have higher ionic conductivity and a wider electrochemical stability window. However, they are brittle and have large interface impedance with electrodes. Compared with inorganic solid electrolytes, polymer solid electrolytes are light in weight, easy to form films, and have good interface compatibility. However, their low ionic conductivity and poor mechanical and electrochemical stability limit their practical applications. CPE-type electrolytes, which are a combination of inorganic solid electrolytes and polymer solid electrolytes, overcome the defects of inorganic electrolytes and polymer electrolytes, and are considered to be one of the practical directions of solid electrolytes, becoming a hot research topic in solid electrolytes. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a reinforced polyethylene oxide solid electrolyte and a preparation method thereof.

[0007] The present invention first provides a method for preparing a reinforced polyethylene oxide solid electrolyte, comprising the following steps:

[0008] (1) Preparation of three-dimensional framework LLZAO;

[0009] (2) condensing bis-3-methylpropyleneoxypropylated tetramethyldisiloxane with the hydroxyl group in the three-dimensional framework LLZAO obtained in step (1) to obtain a three-dimensional framework LLZAO containing acryl groups;

[0010] (3) Adding mercapto polyethylene glycol thiol, polyethylene oxide, LiTFSI, succinonitrile, and sodium ethoxide into an organic solvent, and adding the three-dimensional framework LLZAO containing acryl groups obtained in step (2) and cerium acrylate, using cerium acrylate as a cross-linking agent to carry out a cross-linking reaction between the thiol groups in the mercapto polyethylene glycol thiol and the acryl groups in the three-dimensional framework LLZAO containing acryl groups, coating the obtained slurry on a template, and removing the organic solvent to obtain the enhanced polyethylene oxide solid electrolyte.

[0011] LiTFSI is an organic electrolyte lithium salt. Succinonitrile is a plasticizer. Sodium ethoxide is an alkaline catalyst to catalyze the addition reaction.

[0012] Preferably, the three-dimensional framework LLZAO is a three-dimensional structure Li a La b Zr c Al d O 12 , where 5.8≤a≤7, 2.8≤b≤3.5, 1.8≤c≤2.5, 0.2≤d≤0.28. Specifically, it can be Li 6.28 La3Zr2Al 0.24 O 12 , Li 5.8 La 2.8 Zr 1.8 Al 0.2 O 12 or Li7La 3.5 Zr 2.5 Al 0.28 O 12 .

[0013] More preferably, the three-dimensional framework LLZAO is prepared using a sacrificial template method, and the specific preparation steps include: dissolving lithium nitrate, lanthanum nitrate, zirconium nitrate, and aluminum nitrate in water to obtain a precursor solution;

[0014] The melamine sponge is soaked in the precursor solution, dried and then calcined to obtain the three-dimensional framework LLZAO.

[0015] More preferably, the calcination temperature is 700-900° C. and the calcination time is 1-2 h.

[0016] Preferably, in step (2), the mass ratio of bis-3-methylpropyleneoxypropylated tetramethyldisiloxane to the three-dimensional framework LLZAO is 1:28.3-43.3.

[0017] Preferably, in step (3), the mass ratio of mercapto polyethylene glycol mercapto, polyethylene oxide, LiTFSI, plasticizer, sodium ethoxide, and cerium acrylate is: 10-20: 15.9-60: 100-120: 10-20: 2-5: 0.5-2.

[0018] Preferably, in step (3), the amount of LLZAO containing a three-dimensional acrylic framework added is 10% to 20% of the total mass.

[0019] Preferably, in step (3), the organic solvent is anhydrous acetonitrile.

[0020] The invention also provides a reinforced polyethylene oxide solid electrolyte prepared by the preparation method.

[0021] Reaction mechanism of the present invention:

[0022] 1. Bis-3-methylacryloxypropylated tetramethyldisiloxane and Li 6.28 La3Zr2Al 0.24 O 12 The hydroxyl groups in the condensation reaction are used to obtain Li 6.28 La3Zr2Al 0.24 O 12 .

[0023] 2. Michael addition reaction: There is an excess of thiol groups in thiol polyethylene glycol, and some of the thiol groups react with the propylene group. The thiol end of the thiol polyethylene glycol first attacks Li 6.28 La3Zr2Al 0.24 O 12 The β carbon atom of the propylene group in the propylene group. The α carbon atom is weakened by conjugation with the electron-withdrawing propylene group and is more susceptible to nucleophilic attack.

[0024] 3. Cross-linking process: Some of the thiol groups in the thiol polyethylene glycol thiol group react with the propylene group in the cerium acrylate to play a cross-linking role. Cerium acrylate acts as a cross-linking agent to cross-link between the thiol group and the propylene group to form a denser polymer network. This step enhances the mechanical stability of the electrolyte and optimizes the transmission path of lithium ions.

[0025] 4. Formation of solid electrolyte: The resulting three-dimensional reinforced polymer network provides excellent lithium ion conductivity and acts as a solid electrolyte in the battery, improving the overall performance and safety of the battery.

[0026] Technical effects of the present invention:

[0027] 1. Improve conductivity: Adding plasticizer succinonitrile can significantly improve ionic conductivity, which is mainly due to the high dielectric constant and plasticizing effect of succinonitrile, which helps the migration of lithium ions in the electrolyte.

[0028] 2. Enhanced interface stability: The multi-level solid electrolyte structure design effectively isolates the direct contact between succinonitrile and the lithium anode, preventing adverse reactions at the interface, thereby extending the service life and stability of the battery.

[0029] 3. Inhibit dendrite growth: Solid electrolytes prevent the growth of lithium dendrites through their physical barrier effect. This is because their higher modulus can effectively inhibit the irregular diffusion of lithium in the electrolyte and improve the safety of the battery. DETAILED DESCRIPTION

[0030] Example 1

[0031] A three-dimensional structure Li 6.28 La3Zr2Al 0.24 O 12 The preparation method of the enhanced polyethylene oxide solid electrolyte comprises the following steps:

[0032] A. Synthesis of Li using sacrificial template method 6.28 La3Zr2Al 0.24 O 12 (3D-LLZAO). First, 178.8g LiNO3, 541g La(NO3)3•6H2O, 356.3g Zr(NO3)4•5H2O and 375.13g Al(NO3)3•9H2O were weighed and dissolved in 2000ml deionized water to obtain a 3D-LLZAO precursor solution, in which LiNO3 was added in excess to compensate for the loss of Li during high-temperature sintering. A 3.5×2.5cm melamine sponge was ultrasonically cleaned with ethanol, dried, soaked in the 3D-LLZAO precursor solution, and transferred to an alumina crucible after drying. The temperature was raised at a rate of 2℃•min -1 The temperature was raised to 800 °C and calcined for 2 h. During this process, the sponge template was completely burned to obtain a porous LLZAO framework, which was immediately transferred to a glove box filled with Ar gas for storage.

[0033] B. 3 g of bis-3-methylpropyleneoxypropylated tetramethyldisiloxane (CAS No. 58130-03-3), 1000 g of ethanol, and 130 g of porous LLZAO framework were ultrasonicated at room temperature for 20 minutes, filtered, and dried to obtain propylene-containing 3D-LLZAO; and the 3D-LLZAO was immediately transferred to a glove box filled with Ar gas for storage.

[0034] C. Add 10 g of thiol polyethylene glycol thiol (CAS No. 68865-60-1, molecular formula C4H 10 OS2, M = 138.25), 15.9g polyethylene oxide (PEO, molecular weight 600,000), 100g LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, analytical grade), 10g succinonitrile plasticizer, 2g sodium ethoxide are added to 500g anhydrous acetonitrile, and the propylene-containing 3D-LLZAO prepared in step B and 0.5g 2-acrylic acid cerium salt (CAS No. 94232-55-0) are added at a ratio of 15% of the total mass (the total mass after including the propylene-based 3D-LLZAO, the same below), stirred and dispersed evenly at 70°C, and then coated on a polytetrafluoroethylene template. After volatilization, it is transferred to a vacuum oven for drying. After the solvent is dried, a composite solid electrolyte membrane is finally obtained, and it is stored in a glove box for standby use.

[0035] In this embodiment, the acryl 3D-LLZAO accounts for 15% of the total mass.

[0036] Assembled into a solid-state battery, the test showed that its lithium ion migration number was 0.48 and the discharge specific capacity at 0.1C was 170.1mAh / g.

[0037] Example 2

[0038] A three-dimensional structure Li 5.8 La 2.8 Zr 1.8 Al 0.2 O 12 The preparation method of the enhanced polyethylene oxide solid electrolyte comprises the following steps: the rest is the same as that in Example 1, and the difference from Example 1 is:

[0039] A. The amounts of LiNO3, La(NO3)3•6H2O, Zr(NO3)4•5H2O and Al(NO3)3•9H2O are 179.1g, 519.7g, 343.2g and 375.4g respectively. LiNO3 is added in excess. Transfer to a tube furnace and heat at 700℃ for 1h.

[0040] B. 4.5 g of bis-3-methylacryloxypropylated tetramethyldisiloxane, 1300 g of ethanol, and 150 g of porous LLZAO framework were ultrasonicated at room temperature for 20 minutes, filtered, and dried to obtain 3D-LLZAO containing acrylic groups; and the 3D-LLZAO was immediately transferred to a glove box filled with Ar gas for storage.

[0041] C. Add 15g of mercapto polyethylene glycol thiol (CAS No. 68865-60-1, M=138.25), 40g of polyethylene oxide (molecular weight 600,000), 110g of LiTFSI, 15g of succinonitrile plasticizer, and 3.5g of sodium ethoxide to 550g of anhydrous acetonitrile, add 10% of the total mass of the propylene-containing 3D-LLZAO prepared in step B, and 1g of 2-acrylic acid cerium salt, stir and disperse evenly at 65°C, then apply it to a polytetrafluoroethylene template, transfer it to a vacuum oven for drying after volatilization, wait for the solvent to dry, and finally obtain a composite solid electrolyte membrane, which is stored in a glove box for standby use.

[0042] In this embodiment, the acryl 3D-LLZAO accounts for 10% of the total mass.

[0043] Assembled into a solid-state battery, the test showed that its lithium ion migration number was 0.35 and the discharge specific capacity at 0.1C was 156.4mAh / g.

[0044] Example 3

[0045] A three-dimensional structure of Li7La 3.5 Zr 2.5 Al 0.28 O 12 The preparation method of the enhanced polyethylene oxide solid electrolyte is the same as that in Example 1 except that:

[0046] A. The masses of LiNO3, La(NO3)3•6H2O, Zr(NO3)4•5H2O and Al(NO3)3•9H2O are 186g, 559g, 386g and 750g respectively. LiNO3 is added in excess. Transfer to a tube furnace and heat at 900℃ for 2h.

[0047] B. 6 g of bis-3-methylacryloxypropylated tetramethyldisiloxane, 1600 g of ethanol, and 170 g of porous LLZAO framework were ultrasonicated at room temperature for 20 minutes, filtered, and dried to obtain 3D-LLZAO containing acrylic groups; and the 3D-LLZAO was immediately transferred to a glove box filled with Ar gas for storage.

[0048] C. Add 20g of mercapto polyethylene glycol thiol (CAS No. 68865-60-1, M=138.25), 60g of polyethylene oxide (molecular weight 600,000), 120g of LiTFSI, 20g of succinonitrile plasticizer, and 5g of sodium ethoxide to 600g of anhydrous acetonitrile, add 20% of the total mass of the propylene-containing 3D-LLZAO prepared in step B, and 2g of 2-acrylic acid cerium salt, stir and disperse evenly at 70°C, then apply it to a polytetrafluoroethylene template, transfer it to a vacuum oven for drying after volatilization, wait for the solvent to dry, and finally obtain a composite solid electrolyte membrane, which is stored in a glove box for use.

[0049] In this embodiment, the acryl 3D-LLZAO accounts for 20% of the total mass.

[0050] Assembled into a solid-state battery, the test showed that its lithium ion migration number was 0.26 and the discharge specific capacity at 0.1C was 137.2mAh / g.

[0051] Comparative Example 1

[0052] A three-dimensional structure Li 6.28 La3Zr2Al 0.24 O 12 The preparation method of the enhanced polyethylene oxide solid electrolyte comprises the following steps:

[0053] A. Synthesis of Li using sacrificial template method 6.28 La3Zr2Al 0.24 O 12 (3D-LLZAO). First, 178.8g LiNO3, 541g La(NO3)3•6H2O, 356.3g Zr(NO3)4•5H2O and 375.13g Al(NO3)3•9H2O were weighed and dissolved in 2000ml deionized water to obtain a 3D-LLZAO precursor solution, in which LiNO3 was added in excess to compensate for the loss of Li during high-temperature sintering. A 3.5×2.5cm melamine sponge was ultrasonically cleaned with ethanol, dried, soaked in the 3D-LLZAO precursor solution, and transferred to an alumina crucible after drying. The temperature was raised at a rate of 2℃•min -1 The temperature was raised to 800 °C and calcined for 2 h, during which the sponge template was completely burned to obtain a porous LLZAO framework, which was immediately transferred to an Ar-filled glove box for storage.

[0054] B. Dissolve 15.9g polyethylene oxide (molecular weight 600,000), 100.5g LiTFSI and 2.8g SN (plasticizer) in 400mL anhydrous acetonitrile to form a homogeneous solution (PEO / LiTFSI / SN solution), add the prepared porous LLZAO to the PEO / LiTFSI / SN solution and disperse evenly. Then drop the electrolyte solution onto the polytetrafluoroethylene template, transfer it to a vacuum oven for drying after volatilization, wait for the solvent to dry, where the mass of LLZAO is 15% of the mass of PEO, and finally obtain a composite solid electrolyte membrane, which is stored in a glove box for standby use.

[0055] C. Assembled into a solid-state battery, the test showed that its lithium ion migration number was 0.15 and the discharge specific capacity at 0.1C was 100.1mAh / g.

[0056] It can be seen from the test results of the above embodiments and comparative examples that the present method effectively improves the electrical conductivity and discharge specific capacity of the solid-state battery and prolongs the service life of the battery.

[0057] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a reinforced polyethylene oxide solid electrolyte, characterized in that: The following steps are involved: (1) Preparation of three-dimensional framework LLZAO; (2) condensing bis-3-methylpropyleneoxypropylated tetramethyldisiloxane with the hydroxyl group in the three-dimensional framework LLZAO obtained in step (1) to obtain a three-dimensional framework LLZAO containing acryl groups; (3) Adding mercapto polyethylene glycol thiol, polyethylene oxide, LiTFSI, succinonitrile, and sodium ethoxide into an organic solvent, and adding the three-dimensional framework LLZAO containing acryl groups obtained in step (2) and cerium acrylate, using cerium acrylate as a cross-linking agent to carry out a cross-linking reaction between the thiol groups in the mercapto polyethylene glycol thiol and the acryl groups in the three-dimensional framework LLZAO containing acryl groups, coating the obtained slurry on a template, and removing the organic solvent to obtain the enhanced polyethylene oxide solid electrolyte.

2. The method for preparing the enhanced polyethylene oxide solid electrolyte according to claim 1, characterized in that: The three-dimensional framework LLZAO is a three-dimensional structure Li a La b Zr c Al d O 12 , among which, 5.8≤a≤7, 2.8≤b≤3.5, 1.8≤c≤2.5, 0.2≤d≤0.

28.

3. The method for preparing the enhanced polyethylene oxide solid electrolyte according to claim 2, characterized in that: The three-dimensional framework LLZAO is prepared using a sacrificial template method, and the specific preparation steps include: dissolving lithium nitrate, lanthanum nitrate, zirconium nitrate, and aluminum nitrate in water to obtain a precursor solution; The melamine sponge is soaked in the precursor solution, dried and then calcined to obtain the three-dimensional framework LLZAO.

4. The method for preparing the enhanced polyethylene oxide solid electrolyte according to claim 3, characterized in that: The calcination temperature is 700~900℃, and the calcination time is 1~2h.

5. The method for preparing the enhanced polyethylene oxide solid electrolyte according to claim 1, characterized in that: In step (2), the mass ratio of bis-3-methylpropyleneoxypropylated tetramethyldisiloxane to the three-dimensional framework LLZAO is 1:28.3-43.

3.

6. The method for preparing the enhanced polyethylene oxide solid electrolyte according to claim 1, characterized in that: In step (3), the mass ratio of mercapto polyethylene glycol mercapto, polyethylene oxide, LiTFSI, succinonitrile, sodium ethoxide, and cerium acrylate is: 10~20:15.9~60:100~120:10~20:2~5:0.5~2.

7. The method for preparing the enhanced polyethylene oxide solid electrolyte according to claim 1, characterized in that: In step (3), the amount of LLZAO containing a three-dimensional acrylic framework added is 10% to 20% of the total mass of the obtained slurry.

8. The method for preparing the enhanced polyethylene oxide solid electrolyte according to claim 1, characterized in that: In step (3), the organic solvent is anhydrous acetonitrile.

9. The enhanced polyethylene oxide solid electrolyte prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • LLZO solid electrolyte, composite solid electrolyte and preparation method thereof, and solid-state battery

    CN117525560A

  • Method for rapidly preparing room-temperature cubic phase LLZO solid electrolyte

    CN117878393A

  • Preparation method of linear polyethylene glycol-dendritic poly (thioether-amine) block copolymer

    CN106496587A

  • Lithium lanthanum zirconium oxide solid electrolyte, preparation method thereof and lithium ion battery

    CN109818051A